The role of friends in the opioid epidemic - Adamopoulou, Effrosyni,Greenwood, Jeremy,Guner, Nezih,Kopecky, Karen A. (ZEW - Leibniz Centre for European Economic Research, 2024)
The role of friends in the US opioid epidemic is examined. Using data from the National Longitudinal Survey of Adolescent Health (Add Health), adults aged 25-34 and their high school best friends are focused on. An instrumental variable technique is employed to estimate peer effects in opioid misuse. Severe injuries in the previous year are used as an instrument for opioid misuse in order to estimate the causal impact of a person’s best friends’ opioid misuse on their own misuse. The estimated peer effects are significant: Having a best friend with a reported serious injury in the previous year increases the probability of own opioid misuse by around 7 percentage points in a population where 17 percent ever misuses opioids. The effect is concentrated among non-college graduates and peers with strong ties who are central in their friendship networks. Peer opioid misuse leads to deteriorating health, opioid addiction, and eventually death.
10419/305320
Keywords: Graue Literatur; opioid; peer-group effects; friends; instrumental variables; Add Health; severe injuries